Petrographic, whole-rock geochemical and δ 34S study of the Neoarchaean Black Reef at the Carletonville Goldfield, South Africa: implications for fluid circulation and Au mobilisation - Maselela, Hunadi Kebone Pelican (My University, 2021)
Globally, gold-bearing quartz-pebble conglomerate known as “Witwatersrand-type”, owing their name to the Witwatersrand Basin gold province, occur throughout space and time. In South Africa, outside the Witwatersrand stratigraphy, two examples of the Witwatersrand-type gold deposits exist, namely, the Ventersdorp Contact Reef (VCR) and the Black Reef Formation. The Neoarchaean Black Reef Formation hosts the youngest gold-bearing reef on the Kaapvaal Craton and is mined with some Witwatersrand reefs in the Carletonville goldfield. Presently, little is known about the gold mineralisation mechanism/s in the Black Reef, specifically related to how gold was introduced and why the mineralisation is poorly developed in this part of the stratigraphy. To address these problems, this study uses a combination of petrography, geochemistry, fluid inclusions and S-isotope analyses from four drill cores that intersect the Black Reef in the Carletonville goldfield. There are three main lithologies sampled from the Black Reef in this study: hanging wall carbonaceous shale, footwall quartz arenite and gold-bearing conglomerate commonly referred to as “reef”. The shale units contain a high abundance of total organic carbon, hence the name carbonaceous, and are generally unmineralised with gold. Some parts of these carbonaceous shale units contain graphite, and are embedded with highly fractured quartz-pebbles and authigenic pyrite and contain Au concentration of 1 g/t. They contain relatively high Cr and Ni contents, suggesting that their provenance may be related to mafic lithologies such as the Ventersdorp Supergroup lavas and/or mafic units of greenstone terranes. Quartz arenite units are generally low- to moderately-mineralised with gold (up to 2 g/t Au) but may contain high degrees of pyrite mineralisation (up to 15 % modal abundance) aligned as stringers at bedding foresets and cross-beds. Conglomerate units contain 2 – 28 g/t gold and host significant pyrite mineralisation (up to 30% modal abundance). They are described as well sorted and moderately packed. The matrix of these conglomerate units contain gold- and uranium-bearing, complex shaped carbon nodules that are also located in some quartz fractures. Quartz arenite and conglomerate units contain Zr contents (x̄ = 69.42 ± 16.10 ppm and x̄ = 137.73 ± 85.55 ppm, respectively), Cr contents (x̄ = 140.45 ± 151.85 ppm and x̄ = 201.41 ± 117.33 ppm, respectively) and Al2O3/TiO2 ratios similar to those of various felsic Archean rocks on the Kaapvaal Craton and the underlying sedimentary rocks of the Witwatersrand Supergroup The Black Reef contains carbonaceous material in the form of pyrobitumen, which is divided into four types: globular, nodular, irregular and fracture filling. The former three types are sub rounded and complex shaped. The difference is that the globular and irregular pyrobitumen contain inclusions of gold and uranium while the nodular is massive. The irregular type is often surrounded by pyrite grains. Based on texture and morphology, five different grouping of pyrite are observed: massive detrital pyrite (DM), random inclusion-bearing detrital pyrite (DIR), concentrically laminated detrital pyrite (DIC), euhedral / subhedral authigenic pyrite (AE) and authigenic pyrite overgrowth (AO). The mean whole-rock δ 34S values of carbonaceous shale is 3.20 ‰ and 3.13 ‰ for conglomerate. These values coincide with δ34S values from pyrite grains sourced from the VCR and Witwatersrand reefs. Gold is commonly located at boundaries of pyrite grains and occurs as irregular-shaped phases in quartz-pebble fractures. Microthermometry analysis showed two-phase Type I fluid inclusions (3:2 liquid to vapour ratio), two-phase Type II fluid inclusions (2:3 liquid to vapour ratio), monophase Type II fluid inclusions (one liquid phase) and three-phase Type IV inclusions. The mean entrapment temperature is 172 ± 30 oC with a low and medium salinity clusters. The composition of the fluids is aqueous, H2O-CO2, H2O-CO2-CH4 and H2O-H2S-CH4. The presence of DIC pyrite indicates that they are sourced from the Witwatersrand reefs and the VCR. The VCR and Witwatersrand reefs contain the most of these concretionary pyrite grains, and their fractured nature in the Black Reef provides evidence for a source outside the Transvaal Basin by mechanical recycling, with a short distance travel for them to preserve their laminate texture. The detrital pyrite grains are also indicative of provenance from a local source, some containing inclusions of gold. The overlap of δ 34S values from whole-rock Black Reef samples with those obtained from previous studies on the Witwatersrand reefs and the VCR suggests that the Black Reef pyrite grains are locally sourced by mechanical recycling of pyrite grains from these precursors. Authigenic pyrite and pyrite overgrowths evoke the presence of hydrothermal fluids that entered the Black Reef Formation. Therefore, it is concluded that Black Reef sediments, pyrite and gold are locally sourced from the underlying strata by mechanical reworking of these sources. Hydrothermal fluids formed from prograde metamorphism due the emplacement of the Bushveld Igneous Complex and the Vredefort meteorite impact event. Previously reworked gold was dissolved in hydrothermal fluids containing H2S derived from a volcanically active atmosphere and transported as Au(HS)2 - through fractures, faults and unconformities at the timing of the Vredefort meteorite impact event. Gold was chemically precipitated by reduction when sulphidation of iron-bearing rocks occurred, consuming the reduced sulphur causing pyritization, and precipitated hydrothermal gold at pyrite grain boundaries and trapped native gold in quartz fractures to further distances
A dissertation submitted in partial fulfilment of the requirements for the degree of Master of Science to the Faculty of Science, School of Geosciences, University of the Witwatersrand, Johannesburg, 2021